2020
DOI: 10.36740/wlek202005109
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Basic Pharmacotherapy in the Prevention of Late Adverse Events After Elective Coronary Artery Bypass Grafting

Abstract: The aim: To determine the role of adherence to the guidelines on basic pharmacotherapy in prevention of late major adverse clinical events (MAEs) in patients with stable CAD for three years following isolated CABG. Materials and methods: A prospective single-centre study included 251 consecutive patients with stable CAD (mean age (61±9) years, 218 (86.9%) males), after isolated CABG. In three years MAЕs occurred in 55 (21.9%) patients. The data on pharmacotherapy at follow-up were obtained in 250 patients: 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A later meta-analysis, which is based on a study of individual patients from three studies comparing routine invasive and selective invasive approaches, showed lower mortality and MI during the 5-year followup (BP 0.81, 95.0 CI 0.71-0.93, p = 0.002), with the most significant difference in high-risk patients. Age, diabetes, history of MI, ST depression, hypertension, body mass index (<25 or> 35 kg / m 2), and treatment strategy were independent predictors of death and MI during follow-up (Dudek et al, 2018;Yepanchintseva et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…A later meta-analysis, which is based on a study of individual patients from three studies comparing routine invasive and selective invasive approaches, showed lower mortality and MI during the 5-year followup (BP 0.81, 95.0 CI 0.71-0.93, p = 0.002), with the most significant difference in high-risk patients. Age, diabetes, history of MI, ST depression, hypertension, body mass index (<25 or> 35 kg / m 2), and treatment strategy were independent predictors of death and MI during follow-up (Dudek et al, 2018;Yepanchintseva et al, 2020).…”
Section: Introductionmentioning
confidence: 96%